2020
DOI: 10.1159/000511655
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Fecal miR-223 and miR-451a as Noninvasive and Specific Biomarkers for Diagnosis of Necrotizing Enterocolitis in Preterm Infants

Abstract: <b><i>Objective:</i></b> The objective of this study is to evaluate the usefulness of fecal microRNA (miR)-223 and miR-451a, as novel noninvasive biomarkers for early diagnosis of necrotizing enterocolitis (NEC) in preterm infants. <b><i>Methods:</i></b> Among the top-listed target miRNAs in our previous differential microarray analysis, miR-223 and miR-451a were quantified in a pilot validation case-controlled study (NEC vs. non-NEC/nonsepsis infants; <i>n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…First, they can be harvested in a completely non-invasive way, even for VLBW, without the significant additional burden for NICU personnel. Second, they are likely to directly reflect the intestinal alterations that precede NEC development, as illustrated by the mucosal release and fecal accumulation of calprotectin and lipocalin2 [ 35 ], methylated TLR4 [ 33 ], microRNAs [ 49 ] and the fluctuation of fecal bile acid levels [ 34 ]. Although bowel movements may be delayed in some VLBW infants, most studies were able to successfully deal with this issue for their stool analyses [ 50 , 51 , 52 ], although, in one study, the low recovery of stool specimens at the time of the NEC acute phase was reported to reduce the clinical value of the test for NEC diagnosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, they can be harvested in a completely non-invasive way, even for VLBW, without the significant additional burden for NICU personnel. Second, they are likely to directly reflect the intestinal alterations that precede NEC development, as illustrated by the mucosal release and fecal accumulation of calprotectin and lipocalin2 [ 35 ], methylated TLR4 [ 33 ], microRNAs [ 49 ] and the fluctuation of fecal bile acid levels [ 34 ]. Although bowel movements may be delayed in some VLBW infants, most studies were able to successfully deal with this issue for their stool analyses [ 50 , 51 , 52 ], although, in one study, the low recovery of stool specimens at the time of the NEC acute phase was reported to reduce the clinical value of the test for NEC diagnosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, they are likely to directly reflect the intestinal alterations that precede NEC development, as illustrated by the mucosal release and fecal accumulation of calprotectin and lipocalin2 [ 35 ], methylated TLR4 [ 33 ], microRNAs [ 49 ] and the fluctuation of fecal bile acid levels [ 34 ]. Although bowel movements may be delayed in some VLBW infants, most studies were able to successfully deal with this issue for their stool analyses [ 50 , 51 , 52 ], although, in one study, the low recovery of stool specimens at the time of the NEC acute phase was reported to reduce the clinical value of the test for NEC diagnosis [ 49 ]. In agreement with the preceding studies, herein, we have obtained a sufficient number of stool samples for each of the three selected periods to test seven of the eight NEC cases up to 10 days before the diagnosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For preterm infants with a gestational age ≤26 + 1 weeks, the sensitivity and specificity of fecal calprotectin at 24 h before the onset of clinical symptoms were 0.89 and 0.87, respectively (30). The fecal calprotectin concentration of patients with NEC was significantly increased by 2.1 times (63). A meta-analysis of ten studies showed that the sensitivity, specificity, diagnostic odds ratio (DOR), and area under the curve (AUC) for the early diagnosis by fecal calprotectin were 0.86, 0.79, 34.78, and 0.92, respectively (33).…”
Section: Calprotectinmentioning
confidence: 97%
“…In recent years, studies have identified some DEGs in infants with NEC. The expression of micro RNA (miR)-223 and miR-451a is upregulated in patients with NEC at disease onset (50,63) and miR-223/nuclear factor I-A axis may play an important role in the pathophysiology of NEC by aggravating inflammation and tissue damage (77). A meta-analysis shows that miR-429/200a/b and miR-141/200c clusters are poorly expressed in patients with NEC.…”
Section: Erentially Expressed Genesmentioning
confidence: 99%
“…In addition, these two fecal miRNAs have also been shown to have positive predictive values (PPVs) that range between 0.19 and 0.20. The PPVs could be greatly increased when miRNA and CRP (Day 1) were used in combination (38). Ng et al also investigated the plasma miRNA expression profiles in the NEC compared to sepsis group and non-NEC/non-sepsis group in a case-control study and found that miR-1290, miR-1246 and miR-375 were increased.…”
Section: Mirnas As Potential Biomarkers For Diagnosis In Necmentioning
confidence: 99%